Healthcare provider's performance monitoring for undercovered population during the Covid-19 epidemic, 2021, Tehran: a cross-sectional study - Fatemeh Sharifi Oroomi; Shokouh Shahrousvand; Mahboobeh Mohammad Hosseini; Narjes Tavakolikia; Saeed Taammoli; Elahe Hesari; Abbas Vosoogh-Moghadam (SpringerOpen, 2023)
Abstract Background Considering the necessity and importance of providing health care to children during the Covid-19 epidemic, this study aims to investigate primary health workers performance for infants under 6 months during the Covid-19 epidemic and parent's satisfaction level with these services. Methods This was a cross-sectional study conducted among the defined population of Tehran University of Medical Sciences. The descriptive analysis focused on frequencies and percentages. A chi-square test was used to compare the categorical data between the studied groups. Results Three-hundred seventy-two participants from two District Health Networks of Islamshahr 90 (24%) and Shahr-e-rey 107 (29%) and South Tehran Health Center 175 (47%) were included in the study. About 45% of 2 months old, 54% of 4 months old, and 42% of 6 months old received full basic healthcare package. Coverage of services such as vaccination and height, weight, and head circumference in all three age groups and health networks was 100%. Training in handwashing, touch the face, and hygiene while breastfeeding (64.4%, p = 0.043) and not to use a pacifier (64%, p = 0.038) in Islamshahr Health Network was significantly less than other health networks. The level of parental satisfaction with the provided services was 90.1%. There is a significant association between the dissatisfaction of the participants and not receiving the services completely (p = 0.000). Conclusion During the Covid-19 pandemic, the quality and quantity of primary health care to children have been declined. The focus of health workers was on essential physical health services for infants, and education was almost neglected during this period.